Pyramidal Neurons of the Zebrafish Tectum Receive Highly Convergent Input From Torus Longitudinalis - DeMarco, Elisabeth; Tesmer, Alexander L.; Hech, Bruna; Kawakami, Koichi; Robles, Estuardo (Frontiers in Neuroanatomy, 2021)
The torus longitudinalis (TL) is a midbrain structure unique to ray finned fish. Although previously implicated in orienting behaviors elicited by changes in ambient lighting, the role of TL in visual processing is not well-understood. TL is reciprocally connected to tectum and is the only known source of synaptic input to the stratum marginalis (SM) layer of tectal neuropil. Conversely, tectal pyramidal neurons (PyrNs) are the only identified tectal neuron population that forms a dendrite in SM. In this study we describe a zebrafish gal4 transgenic that labels TL neurons that project to SM. We demonstrate that the axonal TL projection to SM in zebrafish is glutamatergic. Consistent with these axons synapsing directly onto PyrNs, SM-targeted dendrites of PyrNs contain punctate enrichments of the glutamatergic post-synaptic marker protein PSD95. Sparse genetic labeling of individual TL axons and PyrN dendrites enabled quantitative morphometric analysis that revealed (1) large, sparsely branched TL axons in SM and (2) small, densely innervated PyrN dendrites in SM. Together this unique combination of morphologies support a wiring diagram in which TL inputs to PyrNs exhibit a high degree of convergence. We propose that this convergence functions to generate large, compound visual receptive fields in PyrNs. This quantitative anatomical data will instruct future functional studies aimed at identifying the precise contribution of TL-PyrN circuitry to visual behavior.